Polysaccharides from Laminaria japonica: Structural characteristics and antioxidant activity. (November 2016) - Cui, Chun; Lu, Jianghong; Sun-Waterhouse, Dongxiao; Mu, Lixia; Sun, Weizheng; Zhao, Mouming; Zhao, Haifeng
Abstract: In the present study, polysaccharides from Laminaria japonica (LJPA-P) were investigated for their structural characteristics and antioxidant activity. Three acidic polysaccharides LJPA-P1, LJPA-P2 and LJPA-P3 were obtained from Laminaria japonica by sequential hot water and citric acid extraction, and fractionation by DEAE-Sepharose fast flow chromatography and serial NaCl solution elutions. Results showed that three acidic polysaccharides differed in their monosaccharide compositions, sulfation, glycosidic linkages, molecular weights and antioxidant activities. LJPA-P3 was unique in its high sulfate group and galactose contents, molar ratio of galactose, mannose and fucose (26.1: 1.3: 1) and dominance of 1, 3- and 1-linked galactose, exhibiting remarkably high oxygen radical absorbance capacity (ORAC, 1247.22 μmol Trolox/g) and ABTS radical scavenging activity (up to 70%), which was quite different from those of LJPA-P1 and LJPA-P2. Therefore, brown seaweed Laminaria japonica represents a good source of polysaccharides with significant antioxidant activity. Highlights: Polysaccharides were obtained by a joint extraction of hot water and citric acid. Three polysaccharides LJPA-P1, LJPA-P2 and LJPA-P3 were purified and characterized. LJPA-P3 showed the highest ORAC and ABTS radical cation scavenging activity. Sulfation, monosaccharide composition and glycosidic linkage affected activity. Molecular weight seemed less critical for both the ORAC and ABTS activities.